2020
DOI: 10.3389/fphys.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Population Numbers and Physiological Response of an Invasive and Native Thrip Species Following Repeated Exposure to Imidacloprid

Abstract: Frankliniella occidentalis and F. intonsa are devastating pest insects that target Rosa rugosa, Chrysanthemum morifolium, and Phaseolus vulgaris, which are important economical horticultural plants in China. Meanwhile, R. rugosa and C. morifolium are important cash plants in Kunming, South China. We focus on the population performance of these two thrips species on these three host plants with or without repeated exposure to imidacloprid in Kunming. In the field, the population numbers of F. occidentalis devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(31 reference statements)
3
7
0
Order By: Relevance
“…Zhang et al . reported that imidacloprid treatment significantly up‐regulated the activities of detoxifying enzymes (CarE, AChE and MFO) in both F. occidentalis and F. intonsa 21 . The findings of the present study show that spinetoram exerts similar effects in both species.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Zhang et al . reported that imidacloprid treatment significantly up‐regulated the activities of detoxifying enzymes (CarE, AChE and MFO) in both F. occidentalis and F. intonsa 21 . The findings of the present study show that spinetoram exerts similar effects in both species.…”
Section: Discussionsupporting
confidence: 70%
“…F. occidentalis adapted better to adverse ecological conditions than F. intonsa 3 . Both thrips species adapt to adverse environmental conditions such as elevated CO 2 or insecticides by altering the activities of physiological enzymes 21,49 . The findings of the current study showed that elevated CO 2 decreased SOD activity in both thrip species, but increased POD and CAT activity.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The activities of SOD, POD, CAT, AchE, GST, and CarE were determined according to the kit instructions (Beijing Solarbio Science & Technology Co., Ltd., Beijing, China). The enzyme activity was calculated based on the sample mass using UV-Vis spectrophotometry (Zhang et al, 2020). Each treatment comprised 3 replicates.…”
Section: Methodsmentioning
confidence: 99%